"Humanising Healthcare Spaces": Report on the Development and Impact of a Music Collaboration Between Community Music and Donald Gordon Medical Centre at the University of the Witwatersrand, Johannesburg, South Africa. Issue 2 (3rd July 2017) - Harrop-Allin, Susan; Hume, Victoria; Fabian, June; Etheredge, Harriet; McCallum, Michael
ABSTRACT: This article reports on the evaluation of a new partnership between the University of the Witwatersrand's Wits Donald Gordon Medical Centre (WDGMC) and the Music Division at the Wits School of Arts (WSOA) in Johannesburg, South Africa. Established in 2015, the partnership aims to bring live music to the wards of WDGMC through a student placement in the hospital, which forms part of the Bachelor of Music students' fourth year Community Music course. The article examines the effects of live music performances on patients, staff, and hospital spaces more broadly. Data was collected by means of a questionnaire, nurse, and student focus groups, as well as student academic essays. The results revealed a range of benefits and suggest that live music performances may be able to humanise hospital spaces, enabling different modes of musical engagements that confer agency and control to patients, their carers, and nurses. The article concludes by advocating for a mutually-beneficial relationship between the health sciences and the arts, through community music interventions such as this pilot Wits "music in hospital" project.